Improving of wear resistance of screw parts by plasma surfacing by powdered materials - Прасолов, Євген Якович; Бєловол, Світлана Анатоліївна; Багмет, Станіслав Олександрович; Федій, Богдан Сергійович (Technology audit and production reserves, 2015)
The use of reverse polarity plasma surfacing of the screw parts for the equipment of the processing enterprises of agricultural production and the results of our research in this area are discussed in this article. The main purpose of the research is the substantiation of the method of plasma surfacing of cylindrical equipment parts of the processing enterprises of agricultural production. The modern instruments and methods are used during research. The results of staged experiments provided the basis for the selection of the factors for matrix planning of laboratory tests in determining the geometric parameters of the deposited layer on the surfacing modes. The method of plasma surfacing by the powdered mixture, which provides the required mechanical properties of the deposited layer and offers for reclamation of the details of the processing equipment of agricultural enterprises, is proved. The tests at the company confirmed the results of laboratory tests to ensure the durability and quality of the deposited layers of detail.